Role of hemolysis in red cell adenosine triphosphate release in simulated exercise conditions in vitro - Mairbäurl, Heimo; Ruppe, Florian Ansgar; Bärtsch, Peter (Medicine and science in sports and exercise, 2013)
Introduction - Specific adenosine triphosphate (ATP) release from red blood cells has been discussed as a possible mediator controlling microcirculation in states of decreased tissue oxygen. Because intravascular hemolysis might also contribute to plasma ATP, we tested in vitro which portion of ATP release is due to hemolysis in typical exercise-induced strains to the red blood cells (shear stress, deoxygenation, and lactic acidosis). - Methods - Human erythrocytes were suspended in dextran-containing media (hematocrit 10%) and were exposed to shear stress in a rotating Couette viscometer at 37°C. Desaturation (oxygen saturation of hemoglobin ∼20%) was achieved by tonometry with N2 before shear stress exposure. Cells not exposed to shear stress were used as controls. Na lactate (15 mM), lactic acid (15 mM, pH 7.0), and HCl (pH 7.0) were added to simulate exercise-induced lactic acidosis. After incubation, extracellular hemoglobin was measured to quantify hemolysis. ATP was measured with the luciferase assay. - Results - Shear stress increased extracellular ATP in a stress-related and time-dependent manner. Hypoxia induced a ∼10-fold increase in extracellular ATP in nonsheared cells and shear stress-exposed cells. Lactic acid had no significant effect on ATP release and hemolysis. In normoxic cells, approximately 20%-50% of extracellular ATP was due to hemolysis. This proportion decreased to less than 10% in hypoxic cells. - Conclusions - Our results indicate that when exposing red blood cells to typical strains they encounter when passing through capillaries of exercising skeletal muscle, ATP release from red blood cells is caused mainly by deoxygenation and shear stress, whereas lactic acidosis had only a minor effect. Hemolysis effects were decreased when hemoglobin was deoxygenated. Together, by specific release and hemolysis, extracellular ATP reaches values that have been shown to cause local vasodilatation.